Hubungan antara Self-Efficacy Akademik dengan Hasil Belajar Siswa - Hardianto, Gusriko; Erlamsyah, Erlamsyah; Nurfahanah, Nurfahanah (Konselor, 2014)
The students who had high academic self-efficacy, generally, were able to obtain high learning achievement and vise versa. In fact, there were still some students having low academic self-efficacy. This research was aimed at describing the students’ academic self-efficacy and their learning achievement, and revealing the correlation between academic self-efficacy and the students’ learning achievement  at SMA Negeri 2 Solok Selatan. This was a descriptive correlational research. The number of the population was 388 students from which 153 were taken as the sample. The intruments of the research was questionnaire and document of students’ score in mid semester test in academic year 2013-2014. The result of the research indicated that there was a significant correlation between the academic self-efficacy and the students’ learning achievement.